Sodium-ion battery negative electrode material and preparation method and application thereof

By covering carbon nanomaterials on the hard carbon surface of the negative electrode material of the sodium ion battery, artificial SEI film is solved, and the first-term effect, specific capacity and cycling performance of the battery are significantly improved.

CN119812249APending Publication Date: 2025-04-11HUNAN XINGFEIYUE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411891985.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The initial Coulombic efficiency (ICE) of hard carbon, the negative electrode material of existing sodium ion batteries, leads to irreversible capture of sodium ions in the hard carbon matrix and the formation of solid electrolyte interface (SEI) layers, affecting the energy density and cycling stability of the battery.

Method used

By coating carbon nanomaterials on the surface of the hard carbon material, artificial SEI film is constructed, and the π-π conjugated polymer chains of the conductive polymer are used to improve electronic conductivity and electrochemical stability, protect the closed-cell structure of the hard carbon material, and reduce the reaction with the electrolyte.

Benefits of technology

The first-effect, specific capacity and cycling performance of the negative electrode material of sodium ion battery are significantly improved, the conductivity and cycling stability of the material are enhanced, and the process steps are simplified and production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812249A_ABST
    Figure CN119812249A_ABST
Patent Text Reader

Abstract

The invention belongs to a sodium-ion battery negative electrode material, and particularly relates to a sodium-ion battery negative electrode material as well as a preparation method and application thereof. The invention provides a sodium ion battery negative electrode material, which adopts a mode of coating a carbon nanomaterial on the surface of hard carbon to prepare an artificial SEI film so as to solve the reaction between groups on the surface of the hard carbon and an electrolyte. The adopted polymer has a high pi-pi conjugated polymer chain, belongs to a conductive polymer and is good in electronic conductivity; the electrochemical stability is high, and degradation is almost avoided in the battery circulation process; the structure is compact, the integrity of the hard carbon closed pore structure can be maintained from the perspective of physical limitation, and the cycle stability of the hard carbon material can be maintained. The prepared negative electrode material has higher first efficiency, larger specific capacity and excellent cycle performance, and meanwhile, the process steps are simple and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode material for a sodium ion battery, and in particular to a negative electrode material for a sodium ion battery, a preparation method thereof and an application thereof. Background Art

[0002] Hard carbon (HC) is a promising anode material for sodium-ion batteries. + ions, depending on their nanostructures, which depend on the non-stoichiometric chemical composition, including the carbon framework and interstitial pores. Therefore, the capacity of Na-ion batteries can be improved by changing the synthesis conditions to optimize the sodium storage capacity of these structures. The initial Coulombic efficiency (ICE) is closely related to the Na-ion storage performance. In a typical rechargeable Na-ion battery (SIBs) system, ICE is used to measure the reversible migration of Na-ion storage capacity during the first charge and discharge process, which is a key parameter for SIBs anode materials. Low ICE is believed to be due to the irreversible trapping of Na-ions in the HC matrix or the formation of a solid electrolyte interface (SEI) layer. The poor ICE of HC consumes limited Na from the positive electrode side, resulting in a decrease in energy density. Therefore, improving the ICE of HC as a negative electrode is crucial to promote the development of practical applications of Na-ion batteries.

[0003] At present, researchers mainly improve the ICE of hard carbon negative electrodes through high-temperature carbonization or surface coating. Among them, the temperature of high-temperature carbonization is relatively high, often exceeding 1500°C, and the requirements for equipment and energy consumption are very high. Surface coating often uses asphalt as the coating medium, which needs to be heated and carbonized again, and the required energy consumption is also high. More importantly, these two methods have limited effects on improving ICE. Since the SEI film is composed of inorganic salts and organic polymers, if a polymer that is completely coated and conducive to the passage of ions is artificially synthesized on the hard carbon surface, it will greatly reduce the consumption of sodium ions, improve ICE, and help stabilize the cycle performance. Therefore, there is an urgent need to develop a method for constructing an artificial SEI film on the surface of hard carbon particles. Summary of the invention

[0004] In view of the problems existing in the negative electrode materials of sodium ion batteries at this stage, the present invention provides a negative electrode material for sodium ion batteries, which adopts the method of coating carbon nanomaterials on the surface of hard carbon to prepare an artificial SEI film to solve the reaction between the hard carbon surface groups and the electrolyte. The polymer used has a high π-π conjugated polymer chain, which is a conductive polymer with good electronic conductivity; it has high electrochemical stability and almost no degradation during the battery cycle; it has a dense structure and can maintain the integrity of the hard carbon closed-pore structure from the perspective of physical limitations, which helps to maintain the cyclic stability of the hard carbon material. The prepared negative electrode material has higher first efficiency, larger specific capacity and excellent cycle performance, and its process steps are simple and efficient.

[0005] The technical solution of this application is as follows:

[0006] A negative electrode material for a sodium ion battery comprises a hard carbon material and an artificial SEI film wrapped on the surface of the hard carbon material.

[0007] Preferably, the hard carbon material is at least one of coconut shell hard carbon, cotton hard carbon, eucalyptus hard carbon, nanmu hard carbon, bamboo hard carbon, asphalt hard carbon, and phenolic resin hard carbon.

[0008] Another object of the present invention is to protect the preparation method of the above-mentioned sodium ion battery negative electrode material, comprising the following steps:

[0009] The raw materials are mixed to obtain solution A, which is mixed with an ammonium persulfate solution for reaction, filtered, washed, dried, and polymerized to obtain;

[0010] The raw materials include solvent, hard carbon material, nano carbon material, phytic acid solution and conductive polymer.

[0011] Preferably, the solvent comprises alcohol, preferably, the alcohol comprises isopropanol;

[0012] And / or, the conductive polymer is at least one of polypyrrole, polyaniline, and polythiophene polymers;

[0013] And / or, the nano-carbon material is at least one of graphene and carbon nanotube.

[0014] Preferably, the mass ratio of the added amount of the nano-carbon material to the hard carbon material is:

[0015] And / or, the mass ratio of the added amount of the conductive polymer to the hard carbon material is:.

[0016] Preferably, the temperature of the mixing reaction is 0-60°C.

[0017] Preferably, the drying is carried out by spray drying; preferably, during the spray drying process, the parameter is set to 0.3-0.7 MPa, and when the compressed air pressure is 0.2-0.5 MPa, the average droplet diameter is 10-60 μm.

[0018] Preferably, the polymerization conditions are: high temperature heating at 50-150° C. and heat preservation for 1-5 hours under an inert gas atmosphere;

[0019] Preferably, the inert gas includes nitrogen and argon; further, the high temperature heating process is performed at a heating rate of 2-10°C / min.

[0020] Another object of the present invention is to protect the use of the above-mentioned sodium ion battery negative electrode material or the sodium ion battery negative electrode material prepared by the above-mentioned preparation method in sodium ion batteries.

[0021] Furthermore, a sodium sheet is used as the positive electrode, and copper foil and aluminum foil are used as current collectors for the negative electrode and the positive electrode.

[0022] The battery produced by using the negative electrode material of the sodium ion battery of the present invention is tested, with sodium sheet as the positive electrode, copper foil and aluminum foil as the current collectors of the negative electrode and the positive electrode respectively, Celgard2300 type diaphragm as the diaphragm, 1M NaPF6 in EC:DMC=1:1 electrolyte produced by Nanjing Mojies Technology Co., Ltd. as the electrolyte, and assembled into a button battery in an argon glove drying box (water content is controlled below <15ppm). The battery produced by the above basic conditions is tested by a computer-controlled tester, the charging current is 0.1C, the discharging current is 0.1C, the charging and discharging voltage range is 0~2.0V, the first discharge specific capacity is above 312mAh / g, the first efficiency is above 90%, and the finished battery has a capacity retention rate of more than 95% after 1000 cycles of charge and discharge at room temperature.

[0023] Beneficial effects of the present invention

[0024] The present invention utilizes carbon nanomaterials coated on the surface of hard carbon to prepare an artificial SEI film, which can not only isolate the hard carbon negative electrode from the electrolyte, reduce the reaction between the hard carbon surface groups and the electrolyte, but also alleviate the volume expansion and improve the conductivity of the hard carbon negative electrode, thereby improving the electrochemical properties of the material in the battery, such as cycle stability, first efficiency, high and low temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is a scanning electron microscope image of the sample of Example 1;

[0027] Figure 2 This is a scanning electron microscope image of the sample of Example 2;

[0028] Figure 3 This is a scanning electron microscope image of the sample of Example 3;

[0029] Figure 4 This is a scanning electron microscope image of the sample of Example 4;

[0030] Figure 5 This is a scanning electron microscope image of the sample of Example 5;

[0031] Figure 6The charge and discharge curve diagram of the sample of the implementation example. DETAILED DESCRIPTION

[0032] Example 1

[0033] A method for preparing a negative electrode material for a sodium ion battery comprises the following steps:

[0034] 1. The raw materials were mixed to form solution A: 500 g of coconut shell hard carbon, 5 g of single-walled carbon nanotubes and 329 mL of 50 wt% phytic acid solution (Sinopharm Chemical Reagent Co., Ltd.) were added to 2.5 L of isopropanol (Shanghai Aladdin Reagent Co., Ltd.), and after stirring evenly, 150 mL of polypyrrole (Shanghai Aladdin Reagent Co., Ltd.) was added to obtain mixture A.

[0035] 2. Dissolve ammonium persulfate in water to form solution B: Dissolve 489 g of ammonium persulfate (Shanghai McLean Biochemical Technology Co., Ltd.) in 2.5 L of deionized water to form a uniform and stable solution B.

[0036] 3. A+B solution mixing reaction: Take 180 mL of B and add it to mixture A. Stir continuously at 60°C for 6 hours. Use a stirrer to stir at a constant speed during the soaking process.

[0037] 4. Spray drying: After soaking, stir and wash with deionized water until neutral, pour into a spray dryer, spray dry and collect the powder.

[0038] 5. High temperature heating: The spray-dried powder is stably polymerized in an inert gas atmosphere, heated to 60°C, with a heating rate of 2°C / min and a holding time of 5h.

[0039] After testing, the hard carbon negative electrode material is powder particles, and its scanning electron microscope image is as follows Figure 1 As shown. The D50 of the hard carbon negative electrode material is 5.6705 μm, and the specific surface area is 3.0791 m 2 / g.

[0040] Embodiment 2:

[0041] The difference from Example 1 is that the hard carbon material described in step 1 is pitch hard carbon; the coating material is multi-walled carbon nanotubes; the polymer is polythiophene; the heating temperature described in step 5 is 100°C, the heating rate is 2°C / min, and the insulation time is 3h.

[0042] After testing, the hard carbon negative electrode material is powder particles, and its scanning electron microscope image is as follows Figure 2 As shown. The D50 of the hard carbon negative electrode material is 7.6326 μm, and the specific surface area is 2.8901 m 2 / g.

[0043] Example 3

[0044] The difference from Example 1 is that the hard carbon material described in step 1 is phenolic resin hard carbon; the coating material is graphene; the polymer is polypyrrole; the high-temperature heating temperature described in step 5 is 150°C, the heating rate is 2°C / min, and the insulation time is 1h.

[0045] After testing, the hard carbon negative electrode material is a powder particle with D50 = 2.9098 μm and a specific surface area of ​​2.457 m 2 / g.

[0046] Example 4

[0047] The difference from Example 1 is that the hard carbon material in step 1 is eucalyptus hard carbon; the coating material is graphene; the polymer is polythiophene; the high temperature heating temperature in step 5 is 100°C, the heating rate is 2°C / min, and the holding time is 3h.

[0048] After testing, the hard carbon negative electrode material is a powder particle with a D50 of 9.5742 μm and a specific surface area of ​​7.6313 m 2 / g.

[0049] Example 5

[0050] The difference from Example 1 is that: the hard carbon material described in step 1 is asphalt hard carbon; the coating material is graphene; the polymer is polyaniline; the high-temperature heating temperature described in step 5 is 100°C, the heating rate is 2°C / min, and the insulation time is 3h.

[0051] After testing, the hard carbon negative electrode material is a powder particle with a D50 of 7.2948 μm and a specific surface area of ​​3.523 m 2 / g.

[0052] Implementation effect example

[0053] The materials obtained in Examples 1-5 were used as negative electrode active materials, and were uniformly mixed in a mass ratio of negative electrode active material: conductive carbon black SP: sodium carboxymethyl cellulose CMC: styrene-butadiene rubber SBR = 95:1:2:2, and then coated on a copper foil current collector. After drying, a negative electrode sheet was obtained for use.

[0054] The battery produced by the sodium ion battery negative electrode material of the present invention was tested, with sodium sheet as the positive electrode, copper foil and aluminum foil as the current collectors of the negative electrode and the positive electrode respectively, Celgard2300 type diaphragm as the diaphragm, 1M NaPF6 in EC:DMC=1:1 electrolyte produced by Nanjing Mojies Technology Co., Ltd. as the electrolyte, and button batteries were assembled in an argon glove drying box (water content was controlled to be less than 15ppm). The battery produced by the above basic conditions was tested by a computer-controlled tester, with a charging current of 0.1C, a discharging current of 0.1C, and a charge and discharge voltage range of 0~2.0V.

[0055] The performance of the sodium electric hard carbon materials prepared in the above examples 1-5 was tested, and the test results are shown in the following table:

[0056]

[0057] From the test results in the above table (all the above results are average values), it can be seen that after further restriction of the above parameters, the sodium electric hard carbon coating material obtained in the first embodiment has the best comprehensive performance. Under the test conditions of charging current of 0.1C, discharging current of 0.1C, and charging and discharging voltage range of 0-2.0V, its first discharge specific capacity is above 312mAh / g, the first efficiency is above 90%, and the finished battery has a capacity retention rate of more than 95% after 1000 cycles of charge and discharge at room temperature.

[0058] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A sodium ion battery negative electrode material, characterized in that: It includes a hard carbon material and a SEI film wrapped on the surface of the hard carbon material.

2. The sodium ion battery negative electrode material according to claim 1, characterized in that The hard carbon material is at least one of coconut shell hard carbon, cotton hard carbon, eucalyptus hard carbon, nanmu hard carbon, bamboo hard carbon, asphalt hard carbon, and phenolic resin hard carbon.

3. A method for preparing a negative electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: The following steps are involved: Mixing materials including raw materials to obtain solution A, mixing with ammonium persulfate solution for reaction, filtering, washing, drying, and polymerizing to obtain; The raw materials include solvent, hard carbon material, nano carbon material, phytic acid solution and conductive polymer.

4. The method for preparing a negative electrode material for a sodium ion battery according to claim 3, characterized in that: The solvent comprises alcohol, preferably, the alcohol comprises isopropanol; And / or, the conductive polymer includes at least one of polypyrrole, polyaniline, and polythiophene polymers; And / or, the nano-carbon material includes at least one of graphene and carbon nanotubes.

5. The method for preparing the negative electrode material for a sodium ion battery according to claim 3, characterized in that: The mass ratio of the added amount of the nano carbon material to the hard carbon material is: And / or, the mass ratio of the added amount of the conductive polymer to the hard carbon material is:.

6. The method for preparing a negative electrode material for a sodium ion battery according to claim 3, characterized in that: The temperature of the mixed reaction is 0-60°C.

7. The method for preparing a negative electrode material for a sodium ion battery according to claim 3, characterized in that: The drying is carried out by spray drying; preferably, during the spray drying process, the parameter is set to 0.3-0.7MPa, and when the compressed air pressure is 0.2-0.5MPa, the average droplet diameter is 10-60μm.

8. The method for preparing a negative electrode material for a sodium ion battery according to claim 3, characterized in that: The polymerization conditions are: heating at 50-150° C. under an inert gas atmosphere and keeping the temperature for 1-5 hours; Preferably, the inert gas includes nitrogen and argon; further, the high temperature heating process is performed at a heating rate of 2-10°C / min.

9. Use of the sodium ion battery negative electrode material according to claim 1 or 2 or the sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 3 to 8 in a sodium ion battery.

10. The use according to claim 9, characterized in that: The sodium sheet is used as the positive electrode, and the copper foil and aluminum foil are used as the current collectors of the negative electrode and the positive electrode.

Citation Information

Cited By

  • Hard carbon material coated with conductive polymer coating, preparation method of hard carbon material, negative plate and sodium ion battery

    CN120727803A